Determination of l-cysteine origin on the basis of its δ15N values. (15th September 2018) - Bichon, Emmanuelle; Sitthisack, Parina; Sérée-Vattier, Ludivine; Prévost, Stéphanie; Schiphorst, Anne-Marie; Pouponneau, Karinne; Monteau, Fabrice; Le Bizec, Bruno
Highlights: δ 15 N-EA/IRMS analysis of cysteine. Δδ 15 N of 2‰ between cystine extracted from feathers and from hair. Validation of the methodology based on a LAB GTA 25 requirements. Correlation between cystine origin and δ 15 N/δ 13 C values. Abstract: The majority ofl -cysteine is obtained industrially by hydrolysis of animal materials, such as poultry feathers. Despite widespread belief, there is little evidence that human hair is used as a source material and its use is explicitly banned in the European Union (2000/63/EC decision). We developed an isotope ratio mass spectrometric (EA-IRMS) method to determine carbon and nitrogen isotopic ratio in cysteine preparations and related compounds, e.g. cystine and carbocysteine. A threshold relying on the 15 N/ 14 N was established to differentiate between hair and feathers; a value below 6.6‰ indicates a poultry feathers origin. Global uncertainty of measurement was found to be 0.1‰ for δ 15 N (sample size of 0.5–1.8 mg).